Meningeal Relapse of Nodular Lymphocyte Predominant Hodgkin Lymphoma Transformed to T-Cell/Histiocyte-Rich Large B-Cell Lymphoma: A Case Report - Salvioni Chiabotti, Paolo; Bisig, Bettina; Cairoli, Anne; Hajdu, Steven D.; Lovey, Pierre-Yves; Milowich, Dina; Ziadi, Sonia; Du Pasquier, Renaud; Brouland, Jean-Philippe; de Leval, Laurence (Frontiers in Oncology, 2020)
Central nervous system involvement in Hodgkin lymphoma is extremely rare, especially in nodular lymphocyte predominant Hodgkin lymphoma which usually carries a favorable prognosis, Here we report the case of a young patient with nodular lymphocyte predominant Hodgkin lymphoma, who developed a progressive and fatal neurological deterioration, requiring a very extensive work-up including two biopsies to obtain the diagnosis of T-cell/histiocyte-rich large B-cell lymphoma like transformation. This report, which includes post-mortem analysis, highlights the correlations between clinical, radiological and biological data but also the difficulties encountered in reaching the correct diagnosis.